Overexpression of the ATPase Inhibitory Factor 1 Favors a Non-metastatic Phenotype in Breast Cancer - García-Ledo, Lucía; Nuevo-Tapioles, Cristina; Cuevas-Martín, Carmen; Martínez-Reyes, Inmaculada; Soldevilla, Beatriz; González-Llorente, Lucía; Cuezva, José M. (Frontiers in Oncology, 2017)
Partial suppression of mitochondrial oxidative phosphorylation and the concurrent activation of aerobic glycolysis is a hallmark of proliferating cancer cells. Overexpression of the ATPase Inhibitory Factor 1 (IF1), an in vivo inhibitor of the mitochondrial ATP synthase is observed in most prevalent human carcinomas favoring metabolic rewiring to an enhanced glycolysis and cancer progression. Consistently, a high expression of IF1 in hepatocarcinomas and in carcinomas of the lung, bladder, stomach and in gliomas is a biomarker of bad patient prognosis. In contrast to these findings, we have previously reported that a high expression level of IF1 in breast carcinomas is indicative of less chances to develop metastatic disease. This finding is especially relevant in the bad prognosis group of patients bearing triple-negative breast carcinomas. To investigate the molecular mechanisms that underlie the differential behavior of IF1 in breast cancer progression we have developed the triple-negative BT549 breast cancer cell line that overexpresses IF1 stably. When compared to controls, IF1-cells partially shut-down respiration and enhance aerobic glycolysis. Transcriptomic analysis suggested that migration and invasion were specifically inhibited in IF1 overexpressing breast cancer cells. Analysis of gene expression by qPCR and western blotting indicate that IF1 overexpression supports the maintenance of components of the extracellular matrix and E-cadherin concurrently with the downregulation of components and signaling pathways involved in epithelial to mesenchymal transition. Whereas the overexpression of IF1 in breast cancer cells has no effect in the rates of cellular proliferation and in the cell death response to staurosporine and hydrogen peroxide significantly diminishes the ability of the cells to grow in soft-agar and to migrate and invade when compared to control cells. Overall, the results indicate that IF1 overexpression despite favoring a metabolic phenotype prone to cancer progression in the specific case of breast cancer cells also promotes the maintenance of the extracellular matrix impeding metastatic disease. These findings hence provide a mechanistic explanation to the better prognosis of breast cancer patients bearing tumors with high expression level of IF1.